2015
DOI: 10.1002/cncr.29643
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of testicular germ cell tumors among US men by census region

Abstract: Background The incidence of testicular germ cell tumors (TGCT) in the United States (US) is notably higher among white men than other men. Previously, however, our group reported that rates were rising among Hispanics in certain areas. To determine whether this finding was evident in a wider area of the US, data from 39 US cancer registries were examined. Methods Racial/ethnic-specific incidence rates per 100,000 man-years were calculated overall and by census region for the period 1998–2011. Annual percent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 23 publications
1
23
1
Order By: Relevance
“…Similar to findings from previous studies, the current study indicated that the most pronounced increase in TGCT incidence is among Hispanic men. The 2010 US census reported that the majority of Hispanics in the US are of Mexican ancestry (63.0%), followed by Puerto Rican (9.2%), Cuban (3.5%), Salvadoran (3.3%), Dominican (2.8%), and Guatemalan (2.1%) ancesries .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to findings from previous studies, the current study indicated that the most pronounced increase in TGCT incidence is among Hispanic men. The 2010 US census reported that the majority of Hispanics in the US are of Mexican ancestry (63.0%), followed by Puerto Rican (9.2%), Cuban (3.5%), Salvadoran (3.3%), Dominican (2.8%), and Guatemalan (2.1%) ancesries .…”
Section: Discussionsupporting
confidence: 91%
“…1,3 Although non-Hispanic white (NHW) men have the highest incidence of TGCT, the rate of increase over time has slowed, whereas the incidence among Hispanics has increased. 1,4,5 A previous study by our group examining data from the Surveillance, Epidemiology, and End Results (SEER) program and the National Program of Cancer Registries (NPCR) demonstrated that, between 1998 and 2011, the largest increase in TGCT incidence was experienced by Hispanics, followed by only a slight increase in rates among NHWs. 5 Incidence rates also increased among Asian/Pacific Islander (A/PI) men, but the increase was not significant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation mirrors the lack of ancestral diversity represented in GWAS of chemotherapeutic toxicities despite known differences in allele frequencies and effect sizes among individuals of differing ancestries (82). One reason for this is that several GWAS were performed in testicular cancer survivors, a disease that disproportionately affects white males (83). As such, genetic variants that are associated with varying levels of cisplatin sensitivity in European-based studies may not be relevant in patients of other genetic ancestries, thereby promoting a gap in health disparities.…”
Section: Trends In Relevant Pharmacogenomic Studiesmentioning
confidence: 69%
“…This would represent a mechanism by which the testis "filters" the transmission of pathogenic mutations across generations, although proof of this concept would require the development of ultrasensitive assays to screen large numbers of sperm samples. It is noteworthy that despite the relative abundance of strongly oncogenic mutations in the adult male germline, testicular tumors originating from adult spermatogonia (spermatocytic tumors) are extremely rare, with an incidence of about one per million men and are mostly benign in nature (Ghazarian et al 2015;Giannoulatou et al 2017).…”
Section: Discussionmentioning
confidence: 99%